DNA-mediated reversible capture and release of circulating tumor cells with a multivalent dual-specific aptamer coating network. Issue 37 (18th April 2019) - Lin, Yuhong; Jiang, Lili; Huang, Yuqing; Yang, Yuling; He, Yu; Lu, Chunhua; Yang, Huanghao
Abstract : Reversible isolation and release of circulating tumor cells based on DNA-responsive multivalent dual-aptamer-tethered rolling circle amplification network. Abstract : DNA-triggered reversible isolation and recovery of circulating tumor cells (CTCs) is presented based on a multivalent dual-specific aptamer-tethered rolling circle amplification (MA-RCA) network. The multivalent binding sites endow the MA-RCA network with a strong binding ability towards CTCs, and the repeated cell capture/release processes are also actualized in a noninvasive manner.